Facial asymmetry index in normal young adults. (4th December 2012) - Huang, C. S.; Liu, X. Q.; Chen, Y. R.
Structured Abstract: Objectives: To differentiate a symmetric face from an asymmetric face by analyzing a three‐dimensional (3D) facial image and plotting the asymmetry index (AI) on a facial symmetry diagram. Setting and Sample Population: Sixty healthy Chinese adults (30 men and 30 women, mean age: 27.7 + 4.9 years old) without any craniofacial deformity were recruited on a voluntary basis from a medical center. Material and Methods: A 3D facial image of each participant was captured by a GENEX 3D FACE CAM system. Sixteen facial landmarks, as defined by Farkas, were selected on each 3D facial image. The AI was calculated for each landmark. Results: The norm for the AI varied from 0.76 to 2.82. The landmarks located on the upper face had a smaller AI than the landmarks located on the lower face. A facial symmetry diagram was designed according to the mean, one standard deviation, and 2 standard deviations of AI for each landmark. Conclusions: The 3D facial asymmetry can be documented with AI. The landmarks located on the upper face had a smaller AI than the landmarks located on the lower face. The facial symmetry diagram can identify efficiently the location of asymmetry on a face.